Air toxics and the risk of autism spectrum disorder: the results of a population based case–control study in southwestern Pennsylvania. Issue 1 (December 2015) - Talbott, Evelyn; Marshall, Lynne; Rager, Judith; Arena, Vincent; Sharma, Ravi; Stacy, Shaina
Abstract Background Autism spectrum disorders (ASD) constitute a major public health problem affecting one in 68 children. There is little understanding of the causes of ASD despite its serious social impact. Air pollution contains many toxicants known to have adverse effects on the fetus. We conducted a population based case–control study in southwestern Pennsylvania to estimate the association between ASD and 2005 US EPA modeled NATA (National Air Toxics Assessment) levels for 30 neurotoxicants. Methods A total of 217 ASD cases born between 2005 and 2009 were recruited from local ASD diagnostic and treatment centers. There were two different control groups: 1) interviewed controls (N  = 224) frequency matched by child's year of birth, sex and race with complete residential histories from prior to pregnancy through the child's second birthday, and 2) 5, 007 controls generated from a random sample of birth certificates (BC controls) using residence at birth. We used logistic regression analysis comparing higher to first quartile of exposure to estimate odds ratios (ORs) and 95 % confidence intervals (CI), adjusting for mother's age, education, race, smoking status, child's year of birth and sex. Results Comparing fourth to first quartile exposures for all births, the adjusted OR for styrene was 2.04 (95 % CI = 1.17–3.58, p  = 0.013) for the interviewed case–control analysis and 1.61 (95 % CI = 1.08-2.40, p  = 0.018) for the BC analysis. In the BC comparison, chromium also exhibited an elevated OR of 1.60 (95 % CI = 1.08-2.38, p  = 0.020), which was similarly elevated in the interviewed analysis (OR = 1.52, 95 % CI = 0.87–2.66). There were borderline significant ORs for the BC comparison for methylene chloride (OR = 1.41, 95 % CI = 0.96–2.07, p  = 0.082) and PAHs (OR = 1.44, 95 % CI = 0.98–2.11, p  = 0.064). Conclusions Living in areas with higher levels of styrene and chromium during pregnancy was associated with increased risk of ASD, with borderline effects for PAHs and methylene chloride. These results are consistent with other studies. It is unclear, however, whether these chemicals are risk factors themselves or if they reflect the effect of a mixture of pollutants. Future work should include improved spatiotemporal estimates of exposure to air toxics, taking into account the dynamic movement of individuals during daily life.